1984
DOI: 10.1104/pp.74.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Deficiency Results in Increased Suberization in Endodermis and Hypodermis of Corn Roots

Abstract: ABSTRACIThe composition of the aliphatic components of suberin in the stele and cortex of young corn (Zea mays L.) roots was determined by combined gas-liquid chromatography/mass spectrometry of the LiAID4 depolymerization products. u.-Hydroxy acids were shown to be the major clss of the aliphatic components of both the hypodermal (35%) and endodermal (28%) polymeric materials with the dominant chain length being C24 in the former and C16 in the latter. Suberin, which is thought to be a polymer composed of ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In bean it has been reported that iron deficiency caused both inhibition of suberization and a decrease in the activity of an anionic peroxidase [37 ], and in the roots of corn it has been shown that Mg 2+ deficiency resulted in increased suberization of the cell walls of both the hypodermis and endodermis. Peroxidase activity was also higher in the roots of the Mg 2 + -deficient plants than in control plants [32].…”
Section: Southern Analysismentioning
confidence: 85%
“…In bean it has been reported that iron deficiency caused both inhibition of suberization and a decrease in the activity of an anionic peroxidase [37 ], and in the roots of corn it has been shown that Mg 2+ deficiency resulted in increased suberization of the cell walls of both the hypodermis and endodermis. Peroxidase activity was also higher in the roots of the Mg 2 + -deficient plants than in control plants [32].…”
Section: Southern Analysismentioning
confidence: 85%
“…The fact that the anionic peroxidase is localized in the same region in which the suberin polymer is deposited argues strongly that the peroxidase is involved in the biosynthesis of this polymer and that this peroxidase is most probably involved in the polymerization of the phenolic components, to form the aromatic matrix of suberin. In addition to the earlier suggestions (22,26) many recent reports have demonstrated the presence of aromatic components in suberin enriched preparations from the periderm of wound-healed potato (7), Agave americana crystal idioblasts (12), green cotton fiber (31), the endodermis and hypodermis of corn roots (24), the roots of bean (28), and-the envelopes generated by tomato locule protoplasts (25). Furthermore, histochemical tests showed both lipid and phenolic components in hypodermal and endodermal cell walls of roots (23,27,29) which have been shown chemically and ultrastructurally to be suberized (20).…”
Section: Methodsmentioning
confidence: 99%
“…Although lignification and presence of suberin lamellae might reduce the rate of water and ion uptake, a well developed exodermis should enhance the longevity of the root by helping to maintain ionic relations such as turgor during drought (Cruz et al, 1992), exclusion of Na under salinity stress (Walker et al, 1984 ;Storey & Walker, 1987 ;Reinhardt & Rost, 1995) and favourable Mg balance under Mg deficiency (Pozuelo et al, 1984). Besides ionic relations, passage cells might strongly influence both pathogenic (Kamula et al, 1994) and mycorrhizal (Smith et al, 1989 ;Peterson, 1992) fungal infection of the inner cortex.…”
Section: Costs and Benefits Of The Root Exodermismentioning
confidence: 99%